Architecture Design and Interface Engineering of Self-assembly VS4/rGO Heterostructures for Ultrathin Absorbent - Li, Qi; Zhao, Xuan; Zhang, Zheng; Xun, Xiaochen; Zhao, Bin; Xu, Liangxu; Kang, Zhuo; Liao, Qingliang; Zhang, Yue (Nano-Micro Letters, 2022)
The employment of microwave absorbents is highly desirable to address the increasing threats of electromagnetic pollution. Importantly, developing ultrathin absorbent is acknowledged as a linchpin in the design of lightweight and flexible electronic devices, but there are remaining unprecedented challenges. Herein, the self-assembly VS4/rGO heterostructure is constructed to be engineered as ultrathin microwave absorbent through the strategies of architecture design and interface engineering. The microarchitecture and heterointerface of VS4/rGO heterostructure can be regulated by the generation of VS4 nanorods anchored on rGO, which can effectively modulate the impedance matching and attenuation constant. The maximum reflection loss of 2VS4/rGO40 heterostructure can reach − 43.5 dB at 14 GHz with the impedance matching and attenuation constant approaching 0.98 and 187, respectively. The effective absorption bandwidth of 4.8 GHz can be achieved with an ultrathin thickness of 1.4 mm. The far-reaching comprehension of the heterointerface on microwave absorption performance is explicitly unveiled by experimental results and theoretical calculations. Microarchitecture and heterointerface synergistically inspire multi-dimensional advantages to enhance dipole polarization, interfacial polarization, and multiple reflections and scatterings of microwaves. Overall, the strategies of architecture design and interface engineering pave the way for achieving ultrathin and enhanced microwave absorption materials. Highlights: 1 The self-assembly VS4/rGO heterostructure is constructed to be engineered as ultrathin microwave absorbent through the strategies of architecture design and interface engineering. 2 Microarchitecture and heterointerface synergistically inspire multi-dimensional advantages to enhance microwave absorption performance. 3 The effective absorption bandwidth of 4.8 GHz can be achieved with an ultrathin thickness of 1.4 mm.